Full-Scale Structural and Nonstructural Building System Performance during Earthquakes: Part I – Specimen Description, Test Protocol, and Structural Response. Issue 2 (May 2016) - Chen, Michelle C.; Pantoli, Elide; Wang, Xiang; Astroza, Rodrigo; Ebrahimian, Hamed; Hutchinson, Tara C.; Conte, Joel P.; Restrepo, José I.; Marin, Claudia; Walsh, Kenneth D.; Bachman, Robert E.; Hoehler, Matthew S.; et al.
A landmark experimental program was conducted to advance the understanding of nonstructural system performance during earthquakes. The centerpiece of this effort involved shake table testing a full-scale five-story reinforced concrete building furnished with a broad variety of nonstructural components and systems (NCSs) including complete and operable egress, mechanical and electrical systems, facades, and architectural layouts. The building-NCS system was subjected to a suite of earthquake motions of increasing intensity, while base-isolated and then fixed at its base. In this paper, the major components of the test specimen, including the structure and its NCSs, the monitoring systems, and the seismic test protocol are described in detail. Important response and damage characteristics of the structure are also presented. A companion paper describes the damage observed for the various NCSs and correlates these observations with the structure's response.